US national security in the new global order: from the linkage and expansion to homeland security and anti-terrorism - Montúfar, César (2016)
This article describes and compares the national security strategies of the Bill Clinton and George W Bush administrations. It attempts to clarify how the United States conceives national, world, and global space in each strategy.